2008
DOI: 10.1016/j.jaapos.2008.04.012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Bangerter filters on optotype acuity, Vernier acuity, and contrast sensitivity

Abstract: Purpose Bangerter filters are designed to cause progressive degradation of distance optotype acuity to predicted levels (density label indicating expected decimal acuity) and are used to treat amblyopia and diplopia. Nevertheless, there are few data reporting induced acuity deficits. We investigated the effect of Bangerter filters on distance and near optotype acuity, vernier acuity, and contrast sensitivity. Methods Fifteen subjects with best corrected optotype acuity of at least 20/25 in each eye were blur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 12 publications
(16 reference statements)
6
73
1
1
Order By: Relevance
“…These decrements were on the order of 0.3 logMAR with the 0.2 filter producing a greater deficit of approximately 0.55 logMAR. These results are consistent with previous reports indicating that the midrange filters have very similar 23 and, in some cases, nonmonotonic 21 effects on visual acuity. We found a very similar pattern of results for vernier acuity and, in agreement with previous work, 22,23 the decrement in acuity was correlated with the decrement in vernier acuity suggesting a common action of the microelements within the filters on these two visual functions.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These decrements were on the order of 0.3 logMAR with the 0.2 filter producing a greater deficit of approximately 0.55 logMAR. These results are consistent with previous reports indicating that the midrange filters have very similar 23 and, in some cases, nonmonotonic 21 effects on visual acuity. We found a very similar pattern of results for vernier acuity and, in agreement with previous work, 22,23 the decrement in acuity was correlated with the decrement in vernier acuity suggesting a common action of the microelements within the filters on these two visual functions.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with previous reports indicating that the midrange filters have very similar 23 and, in some cases, nonmonotonic 21 effects on visual acuity. We found a very similar pattern of results for vernier acuity and, in agreement with previous work, 22,23 the decrement in acuity was correlated with the decrement in vernier acuity suggesting a common action of the microelements within the filters on these two visual functions. Importantly, our results for the effect of the 0.2 strength filter on visual acuity are in direct agreement with those found by Rutstein et al 24 who also reported an average visual acuity of 0.55 logMAR (equivalent to 20/71) when children with amblyopia viewed through a 0.2 filter using their nonamblyopic eye.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…They were tested while wearing blur goggles simulating Snellen visual acuities of 20/300, 20/600, and 20/800 (nonoverlapping groups of 10 children at each blur level). Blurring was achieved by attaching Bangerter Occlusion foils (40) to clear safety goggles. Assessing the performance of normally sighted subjects while they were wearing blurring goggles enabled us to titrate the effects of reduced acuity comparable to the Prakash children's postoperative outcomes, separate from nonoptical factors on face classification performance.…”
Section: Significancementioning
confidence: 99%